Barriers and Challenges in Distanced-Learning in Developing World - Ennejie Dawn; Miciendily Molde Laure (Journal La Edusci, 2021)
The purpose of this study is to identify the difficulties and impediments that educational institutions in underdeveloped nations confront. Distance learning is critical to sustaining education during the COVID-19 epidemic. This creates a number of difficulties when implementing remote learning. One of the difficulties encountered is a lack of contact with instructors throughout the learning process, which results in a less effective learning process.